Peran Kepemimpinan Transformasional Dalam Meningkatkan Kepuasan Kerja dan Kinerja Guru - Lisniasari, Lisniasari (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
The aim of this research is to analyze the role of transformational leadership in increasing job satisfaction and teacher performance. Writing this scientific article uses literature study. Data was collected through text studies and relevant research results. Data analysis is carried out in steps, namely. First, the data that has been collected is classified based on the formulation of the problem being studied. Second, analyze the data that has been studied using content analysis. Third, drawing conclusions accompanied by suggestions based on the results of the analysis carried out previously in the first and second steps. Based on the results of the discussion, it can be concluded that the role of transformational leadership in increasing job satisfaction and teacher performance is very effective and efficient. These efforts are applied through education or leadership training to foster teachers who are innovative, reflective, creative and charismatic in carrying out their responsibilities effectively, education or leadership training to foster changes in behavior and the main responsibility of teachers in carrying out their responsibilities effectively, by delegating authority to lead. The ability to manage class administration and create programs, as well as providing education about self-evaluation and authority to carry out activities based on personality and independence, as well as recognizing awards and improving incentive systems, are all very important. In addition, the ability to improve the reward system for good behavior is also important.